First principle-based models in plant suspension cell cultures: a review. (17th November 2017) - Villegas, Adriana; Arias, Juan Pablo; Aragón, Daira; Ochoa, Silvia; Arias, Mario
Abstract: In this work, the development and application of published models for describing the behavior of plant cell cultures is reviewed. The structure of each type of model is analyzed and the new tendencies for the modeling of biotechnological processes that can be applied in plant cell cultures are presented. This review is a tool for clarifying the main features that characterize each type of model in the field of plant cell cultures and can be used as a support on the selection of the more suitable model type, taking into account the purpose of specific research.